Low-temperature adsorption of carbon monoxide on gold surfaces: IR spectroscopy uncovers different adsorption states on pristine and rough Au(111) - Pischel, Jan; Pucci, Annemarie (The journal of physical chemistry. C, Energy, materials, and catalysis, 2015)
The morphology of gold surfaces plays a major role in many domains of contemporary research. Infrared (IR) spectroscopy in combination with carbon monoxide (CO) as a probe adsorbate is able to sensitively monitor differences in the morphology of gold surfaces on an atomic level if CO adsorption on the various surfaces is clarified. Our investigation comprises the first study of CO adsorption on Au(111) under well-defined ultrahigh vacuum conditions at 30 K. We find that CO adsorbs on Au(111) in atop geometry, as has been reported before for a variety of gold surfaces, but a significantly higher frequency of the internal CO stretching vibration is observed, confirming results from recent theoretical studies. Furthermore, the presence of a submonolayer amount of gold adatoms on the Au(111) surface results in the properties of gold surfaces toward CO adsorption at higher temperatures known from the literature. Step-wise annealing of these atomically rough surfaces leads to a gradual transition between the literature case and the behavior observed on the pristine Au(111) surface at 30 K.